Executive Functioning in a HIV-positive Paediatric Sample - Mes, Nike (University of the Witwatersrand, Johannesburg, 2024)
High prevalence of Human Immunodeficiency Virus (HIV) poses significant public health challenges in regions like Sub-Saharan Africa, especially among children and adolescents. Despite advancements in reducing vertical mother-to-child transmission and increasing access to antiretroviral therapies, paediatric populations continue to face substantial neurocognitive challenges associated with HIV infection. This study aimed to establish a profile of executive functioning in a South African paediatric population using cognitive measures (the NEPSY-II) and a behavioural rating scale (the BRIEF) to elucidate the cognitive impact of HIV. Assessing executive functions in children presents challenges due to their multifaceted nature, with cognitive measures and behavioural rating scales offering differing insights. As such, a secondary aim of this paper was to examine the inter-correlations between these measures. The participant group was comprised of 40 children living with HIV in Johannesburg, South Africa, aged 10-16. Normative data for comparisons were obtained from the NEPSY-II and BRIEF manuals, as well as a sample of NEPSY-II raw scores for South African youth without a central nervous system disease (Truter et al., 2017). Significant differences were found between the HIV+ group and comparison samples. Specifically, HIV+ children showed poorer performance in working memory, inhibitory control and cognitive flexibility compared to their typically developing peers. These results provide insights into executive function challenges faced by HIV+ children and adolescents, emphasising the importance of early intervention and support.
A research report submitted in fulfillment of the requirements for the Master of Arts in Psychology (Cognitive Science), In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; HIV; Paediatric populations; Neurocognitive challenges; Executive Functioning (EF); South African; Cognitive measures; Behavioural rating scale; Cognitive flexibility; Inhibitory Control; Working Memory; SDG-3: Good health and well-being